Nonparametric identification of the classical errors-in-variables model without side information - Susanne M. Schennach; Yingyao Hu; Arthur Lewbel (Centre for Microdata Methods and Practice (cemmap), 2007)
This note establishes that the fully nonparametric classical errors-in-variables model is identifiable from data on the regressor and the dependent variable alone, unless the specification is a member of a very specific parametric family. This family includes the linear specification with normally distributed variables as a special case. This result relies on standard primitive regularity conditions taking the form of smoothness and monotonicity of the regression function and nonvanishing characteristic functions of the disturbances.
Keywords: 330; Nichtparametrisches Verfahren; Regression; Statistischer Fehler; Instrumentalvariablen-Schätzmethode; Theorie